Implementation of international experience in land resource management - Lopatka, Oksana (Global Prosperity, 2023)
With the launch of the land market, land surveying enterprises have faced the necessity of adapting their activities to a new institutional environment, primarily shaped by the lifting of the moratorium on the sale of agricultural land, which significantly expanded their range of services. Legislative changes require enterprises to react quickly and be prepared to train personnel involved in land rights registration and land management. Adapting to new requirements also includes integrating modern information systems for managing cadastre and land plot registration, which has become critical for ensuring transparency in transactions. Eastern European countries, where the land market was opened after the end of the socialist era and the transition from a planned to a market economy, undertook comprehensive land reform, which included privatizing state lands and introducing land circulation with certain quantitative and price restrictions. Land surveying enterprises in these countries played a key role in implementing the new land ownership system. A particularly important task was adapting land management and updating cadastral data, as most lands did not have clearly defined owners or their rights were disputed after the socialist period. Enterprises carried out the technical inventory of land plots, created cadastral maps, and conducted land assessments for sale. In addition, land surveying enterprises became key participants in the process of integrating national land cadastres into European systems on the path to European Union membership. This required improving service quality standards, automating processes, and implementing electronic land registration systems. The international experience of European countries in land management is valuable for Ukraine, particularly in the areas of technological innovations and digitalization, organizational processes, as well as in reforming the land market and implementing effective land resource management.